The role of LDH serum in diagnosis of pancytopenia in Tishreen University Hospital - حسين, فراس; عماد خياط, محمد; بدور , رلا (Latakia University Journal -Medical Sciences Series, 2022)
Background: Pancytopenia is the simultaneous presence of anemia, leukopenia and thrombocytopenia. The etiologies causes pancytopenia varies depending upon factors, egg age, sex, occupation and geographical distribution. Therefore this observation study is carried out over period of one year in our department of hematology, with the aim to identify etiologies of pancytopenia and its manifestation. The goal of the study: Study the role of LDH serum in diagnosis of pancytopenia without doing invasive procedures as Bone Marrow aspiration and biopsy and other laboratory serological studies. Methods: A descriptive and analytical study was conducted for125patients who attended the Hematology Department and Clinic at Tishreen University Hospital and had pancytopenia upon admission in the time period between 2020-2021. Results and discussion: The sample of the study included 125 patients had pancytopenia, the large proportion of tow age groups was over 50 years old(63,2%),the study sample included a variety of different causes of pancytopenia including: Megaloblastic anemia, aplastic anemia, myelodysplastic syndrome, infectious diseases, hypersplenism, infiltrative diseases, in addition to systemic immune diseases. The large samples were for patients with megaloblastic anemia (58,4%). The serum LDH level was determined for all study patients, where elevated levels of serum LDH were determined in patients with megaloblastic anemia as wall percentage of patients with infiltrative and infectious diseases(LDH<900),and the Serum LDH in(64.4%) of megaloblastic anemia sample was more than1200. Patients with pancytopenia were evaluated by mean corpuscular volume (MCV).Most patients with megaloblastic anemia and a small percentage of other causes had a mean corpuscular volume greater than100 (MCV<100). Finally, samples were distributed among these who had high serum LDH (LDH<1200) and (MCV<100), and all causes were megaloblastic anemia. Conclusion: Serum LDH is an important laboratory procedure to evaluate patients with pancytopenia, in addition to mean corpuscular (MCV). As all of the study patients who had a seum LDH more than three times the normal were diagnosed with megaloblastic anemia without the need for invasive procedures such as and bone marrow aspiration and biopsy , and without resorting to other serological test such as serum VitB12 titration.